Method for preparing seawater-erosion-resistant solidified sludge by using geopolymer and application of seawater-erosion-resistant solidified sludge

By adding phosphoric acid solution and metakaolin to marine silt, and using geological polymer curing technology for phosphate metakaolin base, the problem of cement-cured silt being susceptible to seawater erosion is solved, and cured silt with high strength, compressive resistance and seawater erosion is achieved, and the resource utilization of silt is promoted.

CN119504162APending Publication Date: 2025-02-25HOHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411606440.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing cement-cured sludge is susceptible to seawater erosion, affecting the curing effect and long-term corrosion resistance.

Method used

The phosphate solution and metakaolin are used to add marine silt to the phosphate metakaolin base, and the curing strength and corrosion resistance of the silt are improved through the geological polymer curing technology of the phosphate metakaolin base.

Benefits of technology

The cured sludge after treatment has high compressive strength, good water stability and strong seawater erosion resistance. It is suitable as a foundation treatment material, reducing pollution emissions and promoting the resource utilization of sludge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504162A_ABST
    Figure CN119504162A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing seawater-erosion-resistant solidified sludge by using a geopolymer and application. The method comprises the following steps: pretreating marine silt; preparing a dilute phosphoric acid solution, adding water into strong phosphoric acid, stirring and diluting to obtain the dilute phosphoric acid solution with the molar concentration of 10mol / L, and standing; metakaolin and a dilute phosphoric acid solution are sequentially added into the pretreated marine facies sludge, the mixture is fully and evenly stirred, the water-cement ratio is controlled to be 1: 1, a mixture is obtained, the addition amount of the metakaolin accounts for 12%-18% of the dry weight of the marine facies sludge, and the mass ratio of the addition amount of the dilute phosphoric acid to the addition amount of the metakaolin is 1-1.6; and curing the obtained mixture to prepare the phosphoric acid metakaolin-based geopolymer solidified soil, namely the seawater erosion resistant solidified sludge. The method provided by the invention not only can improve the strength and erosion resistance of the cured sludge to a certain extent, but also can reduce energy loss, pollution emission and erosion of seawater ions, and has good economic benefits and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of reprocessing and utilization of marine sludge, and in particular to a method for preparing seawater-resistant and solidified sludge by utilizing geopolymer and its application. Background Art

[0002] Marine silt has become a challenge that needs to be solved in the construction of coastal and port projects due to its high water content, low strength and instability. Treating these silts into stable foundation materials through solidification technology is an important means to ensure the smooth progress of these projects. At present, alkaline silt solidifiers are widely used in the treatment of marine silt. However, marine silt is usually rich in salt, especially chlorides and sulfates, which will react chemically with alkaline solidifiers to form unstable mineral structures, affecting the solidification effect. In addition, alkaline solidifiers react slowly with minerals in silt. Especially in projects that require rapid construction, the delay in solidification strength may lead to a slowdown in construction progress, increase costs and risks. The high content of organic matter in silt is also a major challenge. Organic matter may react with the solidifier to produce harmful substances, or even hinder the solidification reaction, resulting in a weakened solidification effect. At the same time, some organic matter will decompose in an alkaline environment, which may have a negative impact on the environment. In addition, alkaline solidifiers are easily corroded under high salinity conditions, especially chloride ions and sulfate ions in seawater, which will corrode the solidified materials, resulting in a decrease in their strength and durability. In long-term use, materials treated with alkaline curing agents may experience strength loss and cracks, especially in tidal or high humidity environments. These problems require long-term monitoring and optimization to ensure that the cured materials can be used stably for a long time. Although alkaline sludge curing agents have the advantages of high efficiency and economy in some scenarios, the curing effect and long-term anti-erosion performance are poor when treating marine sludge with high salinity content.

[0003] Existing cement and alkaline curing agents are effective in treating river and lake silt with low water content, but their anti-erosion performance is poor when dealing with marine silt with high salinity and high water content. Summary of the invention

[0004] Technical problem to be solved: In view of the problems in the prior art that the existing cement-solidified sludge is easily eroded by seawater, which affects the solidification effect and long-term anti-corrosion performance, the present invention proposes a method and application of preparing seawater-resistant solidified sludge using geopolymers, wherein phosphoric acid solution and kaolin are added to the marine sludge for solidification treatment. The strength of the solidified sludge after treatment is improved, and it has excellent anti-corrosion and corrosion resistance, which can meet the engineering needs of foundation treatment, and can meet the requirements of reducing pollution emissions, thereby promoting the resource utilization of sludge and having good economic and social benefits.

[0005] Technical solution: The first object of the present invention is to provide a method for preparing seawater erosion resistant solidified sludge using geopolymer, the steps are as follows:

[0006] Step 1, pre-treating the marine sludge;

[0007] Step 2: prepare a dilute phosphoric acid solution by adding concentrated phosphoric acid to water and stirring to dilute it to obtain a dilute phosphoric acid solution with a molar concentration of 10 mol / L, and then let it stand;

[0008] Step 3, adding metakaolin and dilute phosphoric acid solution to the pretreated marine sludge in sequence, stirring well and evenly, controlling the water-cement ratio to be 1:1, to obtain a mixture, wherein the amount of metakaolin added is 12% to 18% of the dry weight of the marine sludge, and the mass ratio of the amount of dilute phosphoric acid added to the amount of metakaolin added is 1 to 1.6;

[0009] Step 4: Curing the mixture obtained in step 3 to prepare metakaolin phosphate-based geopolymer-solidified soil, i.e., seawater-resistant solidified sludge.

[0010] Preferably, the pretreatment in step 1 is as follows: the marine sludge is screened through a 1 mm sieve after removing impurities.

[0011] Preferably, the pretreatment in step one is as follows: dewater the screened marine sludge, add a flocculant thereto in an amount of 0.1% to 0.3% of the dry weight of the sludge, stir sufficiently to completely mix the two, discharge the supernatant after standing, and obtain sludge drying soil with a moisture content of 50-70%.

[0012] Preferably, the flocculant is cationic polyacrylamide with a molecular weight of 1200w.

[0013] Preferably, in step 1, the supernatant is discharged after standing for 20-30 hours.

[0014] Preferably, the mass fraction of concentrated phosphoric acid in step 2 is 85%, the molar concentration is 14.6 mol / L, and it is in a liquid and viscous state; and then it is allowed to stand for 24 hours.

[0015] Preferably, the preparation method of metakaolin in step 3 is as follows: kaolin is used as raw material and is prepared by keeping it at 900-1000° C. in a resistance furnace for 25-35 minutes.

[0016] Preferably, the curing conditions in step 4 are: curing at a constant temperature of 20±0.5°C and a relative humidity of ≥95% for 28 days.

[0017] The second object of the present invention is to provide a seawater erosion resistant solidified sludge prepared based on the above method.

[0018] The third object of the present invention is to provide a method for using the anti-seawater erosion solidified silt as a seawater erosion resistant foundation material.

[0019] After a long period of research and practice, the inventors of the present invention finally obtained a phosphate metakaolin-based geopolymer as an alternative curing agent. The curing agent uses phosphoric acid as the acidic activator of the geopolymer and metakaolin as the gelling material of the geopolymer. This new curing agent can maintain good chemical stability in a high salinity and high humidity environment, and can effectively combine with minerals in marine silt to generate a solid structure with higher strength and better durability, thereby improving the curing effect of marine silt. This invention has broad application prospects in practical engineering.

[0020] Beneficial effects:

[0021] 1. The anti-seawater erosion solidified sludge provided by the present invention can achieve the solidification effect by simply stirring each component evenly, which is simple and easy to operate and will not cause pollution to the environment;

[0022] 2. The solidified sludge of the present invention has high compressive strength, good water stability and strong resistance to seawater erosion;

[0023] 3. The curing agent proposed in the present invention is suitable for reinforcing marine silt soft soil, can efficiently recycle marine silt, can develop river and sea resources and tidal flat resources, promote the resource utilization and reduction of silt, and has good economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention is a flow chart for preparing the metakaolin phosphate-based geopolymer-solidified soil;

[0025] Figure 2 is the strength variation curve of the solidified sludge in distilled water of the present invention;

[0026] Figure 3 is the strength variation curve of the solidified sludge in natural seawater of the present invention;

[0027] Figure 4 This is the strength variation curve of the solidified sludge in high-concentration salt water of the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. However, it should not be construed as limiting the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the method, steps or conditions of the present invention all fall within the scope of the present invention.

[0029] The present invention provides a method for preparing seawater erosion resistant solidified sludge using geopolymer, see Figure 1 , the steps are as follows:

[0030] Step 1, pre-treating the marine sludge;

[0031] Step 2: prepare a dilute phosphoric acid solution by adding concentrated phosphoric acid to water and stirring to dilute it to obtain a dilute phosphoric acid solution with a molar concentration of 10 mol / L, and then let it stand;

[0032] Step 3, adding metakaolin and dilute phosphoric acid solution to the pretreated marine sludge in sequence, stirring well and evenly, controlling the water-cement ratio to be 1:1, to obtain a mixture, wherein the amount of metakaolin added is 12% to 18% of the dry weight of the marine sludge, and the mass ratio of the amount of dilute phosphoric acid added to the amount of metakaolin added is 1 to 1.6;

[0033] Step 4: Curing the mixture obtained in step 3 to prepare metakaolin phosphate-based geopolymer-solidified soil, i.e., seawater-resistant solidified sludge.

[0034] As a further preferred embodiment, the pretreatment in step 1 is specifically as follows: the marine sludge is filtered through a 1 mm sieve after removing impurities.

[0035] As a further preferred embodiment, the pretreatment in step one is specifically as follows: dewater the screened marine sludge, add a flocculant thereto, the amount of the flocculant added is 0.1% to 0.3% of the dry weight of the sludge, stir them thoroughly to completely mix the two, discharge the supernatant after standing, and obtain sludge drying soil with a moisture content of 50-70%.

[0036] As a further preferred embodiment, the flocculant is cationic polyacrylamide with a molecular weight of 1200w.

[0037] As a further preferred embodiment, in the step 1, the supernatant is discharged after standing for 20-30 hours.

[0038] As a further preferred embodiment, in the step 2, the mass fraction of concentrated phosphoric acid is 85%, the molar concentration is 14.6 mol / L, and it is in a liquid and viscous state; and then it is allowed to stand for 24 hours.

[0039] As a further preferred embodiment, the preparation method of the metakaolin in step three is as follows: kaolin is used as a raw material and is prepared by keeping it at 900-1000° C. in a resistance furnace for 25-35 minutes.

[0040] As a further preferred embodiment, the curing conditions in step 4 are: curing at a constant temperature of 20±0.5°C and a relative humidity of ≥95% for 28 days.

[0041] A seawater erosion resistant solidified sludge prepared based on the above method.

[0042] The invention discloses an application of seawater erosion resistant solidified silt as a seawater erosion resistant foundation material.

[0043] Specifically, in the embodiments of this specification:

[0044] The marine silt comes from Lianyungang, Jiangsu Province. The original water content is 68.7% and the density is 1.51g / cm 3 , liquid limit 49.4%, plastic limit 25.4%. The pretreatment is as follows: remove impurities (shellfish, etc.) from the marine sludge and pass it through a 1mm sieve, then add 0.1% to 0.3% of the dry weight of the sludge flocculant, stir well to make the two completely mixed, let it stand for 24 hours, discharge the supernatant, and obtain a dried marine sludge soil with a moisture content of 55±5%.

[0045] The phosphoric acid solution is prepared by diluting concentrated phosphoric acid having a molar concentration of 14.6 mol / L and a mass fraction of 85% with water, and the molar concentration is 10 mol / L.

[0046] Metakaolin is prepared by using kaolin as raw material and keeping it at 950℃ in a resistance furnace for 30 minutes.

[0047] The solidified sludge prepared in the embodiment of the present invention is cured and then corroded in a prepared solution for a period of time by a solution immersion method. The strength retention rate and mass change rate before and after the immersion are used to characterize its anti-corrosion performance.

[0048] The comparative example is a cement-solidified soil obtained by solidifying the same amount of the sludge with 12% PO42.5 ordinary Portland cement. After curing, it is corroded in the prepared solution for a period of time by the solution immersion method. The strength retention rate and mass change rate before and after immersion are used to characterize its anti-corrosion performance.

[0049] Among them, the curing conditions are 20±0.5℃, relative humidity ≥95%, the curing age is 3d, 7d, 14d, 28d, and 56d, the erosion solution types are distilled water, prepared natural seawater, and prepared high-concentration seawater, and the erosion time is 3d, 7d, 14d, and 28d.

[0050] The method for preparing natural seawater is to add NaCl, CaSO4 and CaCO3 to distilled water and leave it for one day, then add MgCl2 and MgSO4 to dissolve and mix evenly before use. The preparation concentration is shown in the following table:

[0051] Table 1 Contents of various salts in prepared natural seawater

[0052] Types of salt NaCl <![CDATA[MgCl2]]> <![CDATA[MgSO4]]> <![CDATA[CaSO4]]> <![CDATA[CaCO3]]> Concentration (g / L) 21.00 2.54 1.54 2.43 0.1

[0053] The method for preparing high-concentration seawater is to add NaCl, CaSO4 and CaCO3 to distilled water and leave it for one day, then add MgCl2 and MgSO4 to dissolve and mix evenly before use. The preparation concentration is shown in the following table:

[0054] Table 2 Salt contents of various types of high-concentration seawater

[0055] Types of salt NaCl <![CDATA[MgCl2]]> <![CDATA[MgSO4]]> <![CDATA[CaSO4]]> <![CDATA[CaCO3]]> Concentration (g / L) 105 12.70 7.70 12.15 0.5

[0056] The strength retention rate R (%) involved in this specification is calculated by the following formula:

[0057]

[0058] Where: f t is the unconfined compressive strength of the sample after 28 days of curing, unit: kPa; f0 is the unconfined compressive strength of the sample after erosion t (time, unit: d), unit: kPa; R is the strength retention rate, %.

[0059] The specific embodiments are as follows:

[0060] Example 1

[0061] This embodiment provides a method for preparing seawater erosion resistant solidified sludge using geopolymer, wherein the components of metakaolin phosphate-based geopolymer (solidifying agent) and the mass fraction ratio of each component are: metakaolin added in an amount of 12% of the dry weight of marine sludge, and phosphoric acid solution added in an amount of 1.3 times the amount of metakaolin. The solidifying agent with the above ratio is added to the dried marine sludge soil, and stirred evenly, and the water-cement ratio is controlled to be 1:1, to obtain metakaolin phosphate-based geopolymer solidified soil, that is, seawater erosion resistant solidified sludge.

[0062] After the anti-seawater erosion solidified silt was cured under standard conditions, its unconfined compressive strength was measured: the strength was 341.9 kPa at 3 days, 631 kPa at 7 days, 689.8 kPa at 14 days, 891.8 kPa at 28 days, and 987.7 kPa at 56 days.

[0063] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in distilled water at 0d, 3d, 7d, 14d and 28d: 891.8kPa at 0d, 933kPa at 3d, 958kPa at 7d, 956.7kPa at 14d and 946kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt in distilled water erosion for 28d was 103.04%.

[0064] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in natural seawater at 0d, 3d, 7d, 14d and 28d: 891.8kPa at 0d, 923.6kPa at 3d, 931.7kPa at 7d, 930.9kPa at 14d and 921.7kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt after 28d of natural seawater erosion was 103.35%.

[0065] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in high-concentration seawater at 0d, 3d, 7d, 14d and 28d: 891.8kPa at 0d, 864.1kPa at 3d, 812.1kPa at 7d, 797.2kPa at 14d, and 782.1kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt after 28 days of high-concentration seawater erosion was 87.7%.

[0066] Comparative Example 1

[0067] Same as Example 1, except that the curing agent is alkaline curing agent PO42.5 ordinary Portland cement. This comparative example uses 12wt% PO42.5 ordinary Portland cement to solidify the same amount of marine silt dried soil to obtain cement-solidified soil. After curing under standard conditions, its unconfined compressive strength is as follows: 225.7 kPa at 3 days, 802.6 kPa at 7 days, 1239.1 kPa at 14 days, 1431.6 kPa at 28 days, and 1562.7 kPa at 56 days;

[0068] After 28 days of curing, the unconfined compressive strength of the soil was 1431.6 kPa at 0 days, 1467.5 kPa at 3 days, 1494.5 kPa at 7 days, 1449.6 kPa at 14 days, and 1396.5 kPa at 28 days after erosion in distilled water for 0 days, 3 days, 7 days, 14 days, and 28 days. The strength retention rate of cement-cured soil eroded by distilled water for 28 days was 97.55%.

[0069] After 28 days of curing, the unconfined compressive strength of the soil was 1431.6 kPa at 0 days, 1398.6 kPa at 3 days, 1351.3 kPa at 7 days, 1316.4 kPa at 14 days, and 1281 kPa at 28 days when it was corroded in natural seawater for 0 days, 3 days, 7 days, 14 days, and 28 days. The strength retention rate of cement-cured soil corroded by natural seawater for 28 days was 89.48%.

[0070] After 28 days of curing, the soil was corroded in high-concentration seawater for 0 days, 3 days, 7 days, 14 days and 28 days. The unconfined compressive strength was as follows: the strength was 1431.6 kPa at 0 days, and it was damaged at 3 days, and its compressive strength could not be measured. The strength retention rate of cement-cured soil corroded by high-concentration seawater for 28 days was 0%.

[0071] Example 2

[0072] This embodiment provides a method for preparing seawater erosion resistant solidified silt using geopolymer, wherein the mass fraction ratio of the components of the metakaolin phosphate-based geopolymer (solidifying agent) is: metakaolin added in an amount of 14% of the dry weight of the marine silt, and a phosphoric acid solution added in an amount of 1.3 times the amount of metakaolin. The solidifying agent with the above ratio is added to the dried marine silt soil, and stirred evenly, and the water-cement ratio is controlled to be 1:1, to obtain metakaolin phosphate-based geopolymer solidified soil, that is, seawater erosion resistant solidified silt.

[0073] After the seawater erosion-resistant solidified sludge was cured under standard conditions, its unconfined compressive strength was measured: the strength at 3 days was 413.5 kPa, the strength at 7 days was 749.3 kPa, the strength at 14 days was 842.5 kPa, the strength at 28 days was 1176.2 kPa, and the strength at 56 days was 1373.5 kPa;

[0074] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in distilled water at 0d, 3d, 7d, 14d and 28d: 1176.2kPa at 0d, 1276.2kPa at 3d, 1318.1kPa at 7d, 1312.7kPa at 14d, and 1295.2kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt in distilled water erosion for 28d was 110.12%.

[0075] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in natural seawater at 0d, 3d, 7d, 14d and 28d: 1176.2kPa at 0d, 1249.4kPa at 3d, 1284.3kPa at 7d, 1271.9kPa at 14d, and 1263.4kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt after 28d of natural seawater erosion was 107.41%.

[0076] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in high-concentration seawater at 0d, 3d, 7d, 14d and 28d. The strength at 0d was 1176.2kPa, at 3d was 1160.7kPa, at 7d was 1150.6kPa, at 14d was 1100.5kPa, and at 28d was 1087.1kPa. The strength retention rate of the anti-seawater erosion solidified silt after 28 days of high-concentration seawater erosion was 92.42%.

[0077] Example 3

[0078] A method for preparing seawater erosion resistant solidified sludge using geopolymer, wherein the components of metakaolin phosphate-based geopolymer (solidifier) ​​and the mass fraction ratio of each component are: metakaolin added in an amount of 16% of the dry weight of marine sludge, and phosphoric acid solution added in an amount of 1.3 times the amount of metakaolin. The solidifier with the above ratio is added to the dried marine sludge soil and stirred evenly, and the water-cement ratio is controlled to be 1:1, to obtain metakaolin phosphate-based geopolymer solidified soil, that is, seawater erosion resistant solidified sludge.

[0079] After the seawater erosion-resistant solidified sludge was cured under standard conditions, its unconfined compressive strength was measured: the strength at 3 days was 450 kPa, the strength at 7 days was 889.1 kPa, the strength at 14 days was 1008.7 kPa, the strength at 28 days was 1358.7 kPa, and the strength at 56 days was 1635 kPa;

[0080] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in distilled water at 0d, 3d, 7d, 14d and 28d: 1358.7kPa at 0d, 1516.7kPa at 3d, 1592.4kPa at 7d, 1585kPa at 14d, and 1547.2kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt in distilled water erosion for 28d was 113.87%.

[0081] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in natural seawater at 0d, 3d, 7d, 14d and 28d: 1358.7kPa at 0d, 1477.6kPa at 3d, 1519.1kPa at 7d, 1501.9kPa at 14d, and 1484.3kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt after 28d of natural seawater erosion was 109.24%.

[0082] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in high-concentration seawater at 0d, 3d, 7d, 14d and 28d: 1358.7kPa at 0d, 1355.9kPa at 3d, 1304.9kPa at 7d, 1289.7kPa at 14d, and 1237kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt after 28d of high-concentration seawater erosion was 91.04%.

[0083] Example 4

[0084] A method for preparing seawater erosion resistant solidified sludge using geopolymer, wherein the components of metakaolin phosphate-based geopolymer (solidifier) ​​and the mass fraction ratio of each component are: metakaolin added in an amount of 18% of the dry weight of marine sludge, and phosphoric acid solution added in an amount of 1.3 times the amount of metakaolin. The solidifier with the above ratio is added to the dried marine sludge soil and stirred evenly, and the water-cement ratio is controlled to be 1:1, to obtain metakaolin phosphate-based geopolymer solidified soil, that is, seawater erosion resistant solidified sludge.

[0085] After the seawater erosion-resistant solidified sludge was cured under standard conditions, its unconfined compressive strength was measured: the strength at 3 days was 541.8 kPa, the strength at 7 days was 1046.5 kPa, the strength at 14 days was 1304.6 kPa, the strength at 28 days was 1901.2 kPa, and the strength at 56 days was 1977.5 kPa;

[0086] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in distilled water at 0d, 3d, 7d, 14d and 28d: 1901.2kPa at 0d, 1932.2kPa at 3d, 1950.5kPa at 7d, 1939.7kPa at 14d, and 1918.2kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt in distilled water erosion for 28d was 100.89%.

[0087] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in natural seawater at 0d, 3d, 7d, 14d and 28d: 1901.2kPa at 0d, 1930.3kPa at 3d, 1948.1kPa at 7d, 1930.5kPa at 14d, and 1916.1kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt after 28d of natural seawater erosion was 100.78%.

[0088] After 28 days of curing, the unconfined compressive strength of the anti-seawater erosion solidified silt was measured in high-concentration seawater at 0d, 3d, 7d, 14d and 28d: 1901.2kPa at 0d, 1888.5kPa at 3d, 1799.8kPa at 7d, 1777.9kPa at 14d, and 1750.1kPa at 28d. The strength retention rate of the anti-seawater erosion solidified silt after 28d of high-concentration seawater erosion was 92.05%.

[0089] The strength change curves of the solidified sludge prepared in the above Examples 1-4 and the cement solidified soil prepared in Comparative Example 1 in distilled water / natural seawater / high-concentration salt water are shown in FIG. Figure 2-4 In the legend, 12% phosphated metakaolin-based polymer corresponds to the solidified sludge prepared in Example 1, 14% phosphated metakaolin-based polymer corresponds to the solidified sludge prepared in Example 2, 16% phosphated metakaolin-based polymer corresponds to the solidified sludge prepared in Example 3, 18% phosphated metakaolin-based polymer corresponds to the solidified sludge prepared in Example 4, and 12% cement corresponds to the cement-solidified soil prepared in Example 1.

[0090] It can be seen from the above examples and comparative examples that under the erosion of distilled water, the strength retention rate of cement-solidified soil is 97.55%. In comparison, the strength retention rate of the solidified sludge (12% phosphate metakaolin-based polymer) prepared in Example 1 reaches 103.04%, which is increased by 5.63%; the strength retention rate of the solidified sludge (14% phosphate metakaolin-based polymer) prepared in Example 2 reaches 110.12%, which is increased by 12.89%; the strength retention rate of the solidified sludge (16% phosphate metakaolin-based polymer) prepared in Example 3 reaches 113.87%, which is increased by 16.73%; the strength retention rate of the solidified sludge (18% phosphate metakaolin-based polymer) prepared in Example 4 reaches 100.89%, which is increased by 3.42%. Therefore, it can be seen that the phosphate metakaolin-based geopolymer has a good anti-erosion effect in the application of solidified sludge. At the same time, its strength retention rate reaches the highest when the addition amount is 16%, proving that its optimal addition amount is 16%.

[0091] Under the action of natural seawater, the strength retention rate of cement solidified soil is 89.48%. In comparison, the strength retention rate of the solidified sludge (12% phosphate metakaolin-based polymer) prepared in Example 1 reaches 103.35%, an increase of 15.5%; the strength retention rate of the solidified sludge (14% phosphate metakaolin-based polymer) prepared in Example 2 reaches 107.41%, an increase of 20.04%; the strength retention rate of the solidified sludge (16% phosphate metakaolin-based polymer) prepared in Example 3 reaches 109.24%, an increase of 22.08%; the strength retention rate of the solidified sludge (18% phosphate metakaolin-based polymer) prepared in Example 4 reaches 100.78%, an increase of 12.63%. It also shows that the phosphate metakaolin-based geopolymer has a good anti-erosion effect in the application of solidified sludge, and its optimal addition amount is 16%.

[0092] Under the action of high-concentration seawater, cement-solidified soil was destroyed on the third day of erosion, and its strength retention rate was 0%. In comparison, the strength retention rate of the solidified sludge (12% phosphate metakaolin-based polymer) prepared in Example 1 reached 87.7%; the strength retention rate of the solidified sludge (14% phosphate metakaolin-based polymer) prepared in Example 2 reached 92.42%; the strength retention rate of the solidified sludge (16% phosphate metakaolin-based polymer) prepared in Example 3 reached 91.04%; the strength retention rate of the solidified sludge (18% phosphate metakaolin-based polymer) prepared in Example 4 reached 92.05%. Therefore, it can be seen that the phosphate metakaolin-based geopolymer has a significant anti-erosion effect under high-concentration seawater conditions. Under this condition, the strength retention rate of the geopolymer reaches the highest when the addition amount is 14%, but since the data difference between 16% and 14% is small, it can still be considered that the addition amount of 16% is the optimal addition amount.

[0093] In summary, the phosphate metakaolin-based geopolymer-based seawater-resistant solidified silt obtained by the method provided by the present invention has a much higher seawater-resistant erosion resistance than the existing cement-solidified soil. The prepared seawater-resistant solidified silt has good erosion resistance, which provides an important basis for the future application of geopolymers in silt solidification projects.

[0094] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned implementation modes, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned implementation modes can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the implementation modes of the present invention.

Claims

1. A method for preparing seawater erosion resistant solidified sludge using geopolymer, characterized in that: Here are the steps: Step 1, pre-treating the marine sludge; Step 2: prepare a dilute phosphoric acid solution by adding concentrated phosphoric acid to water and stirring to dilute it to obtain a dilute phosphoric acid solution with a molar concentration of 10 mol / L, and then let it stand; Step 3, adding metakaolin and dilute phosphoric acid solution to the pretreated marine sludge in sequence, stirring well and evenly, controlling the water-cement ratio to be 1:1, to obtain a mixture, wherein the amount of metakaolin added is 12% to 18% of the dry weight of the marine sludge, and the mass ratio of the amount of dilute phosphoric acid added to the amount of metakaolin added is 1 to 1.6; Step 4: Curing the mixture obtained in step 3 to prepare metakaolin phosphate-based geopolymer-solidified soil, i.e., seawater-resistant solidified sludge.

2. The method for preparing seawater erosion resistant solidified sludge using geopolymer according to claim 1, characterized in that: The pretreatment in step 1 is specifically as follows: the marine sludge is screened through a 1 mm sieve after removing impurities.

3. The method for preparing seawater erosion resistant solidified sludge using geopolymer according to claim 2, characterized in that: The pretreatment in step 1 is as follows: dewater the sieved marine sludge, add a flocculant thereto, the amount of the flocculant added is 0.1% to 0.3% of the dry weight of the sludge, stir well to make the two completely mixed, let stand and discharge the supernatant to obtain a sludge with a water content of 50-70% and a density of 1.5-1.75 g / cm 3 of dried silt soil.

4. The method for preparing seawater erosion resistant solidified sludge using geopolymer according to claim 3, characterized in that: The flocculant is cationic polyacrylamide with a molecular weight of 1200w.

5. The method for preparing seawater erosion resistant solidified sludge using geopolymer according to claim 3, characterized in that: In the step 1, the supernatant is discharged after standing for 20-30 hours.

6. The method for preparing seawater erosion resistant solidified sludge using geopolymer according to claim 1, characterized in that: The mass fraction of concentrated phosphoric acid in the step 2 is 85%, the molar concentration is 14.6 mol / L, and it is in a liquid and viscous state; and then it is left to stand for 24 hours.

7. The method for preparing seawater erosion resistant solidified sludge using geopolymer according to claim 1, characterized in that: The preparation method of the metakaolin in step 3 is as follows: kaolin is used as a raw material and is prepared by keeping it at 900-1000° C. in a resistance furnace for 25-35 minutes.

8. The method for preparing seawater erosion resistant solidified sludge using geopolymer according to claim 1, characterized in that: The curing conditions in step 4 are: curing at a constant temperature of 20±0.5°C and a relative humidity of ≥95% for 28 days.

9. A seawater erosion resistant solidified sludge prepared by the method according to any one of claims 1 to 8.

10. Use of the anti-seawater erosion solidified sludge according to claim 9 as a seawater erosion resistant foundation material.